(untitled) (Academic Journal of Internal Affairs, 2023)
Aim: Today, digitalisation provides opportunities for growth in almost every sector and industry. The Authors analyse the modernisation of state and local public administration and present the advantages and disadvantages of eGovernment. They examine the current situation of disaster management authorities, collect and evaluate the current electronic software, compare them with each other and make recommendations for their improvement on the basis of their conclusions. Methodology: The authors represent the relevant literature on the modernisation of public administrations, showing their advantages and disadvantages, and evaluate the results of the main sources. The authors gather together the electronic software and tools used in the work of public administrations, analyse them, examine their interrelationships and, after the analysis, present their characteristics in a table. Based on their results, they make proposals for further improvements. Findings: The existing specialised systems used by disaster management are becoming increasingly efficient in the administration of disaster management authorities. However, systemic hardware and software improvements are still essential to achieve full eGovernment. Value: The development and deployment of eGovernment is nowadays enhanced by the emerging energy crisis and human resource challenges.